Two hot Jupiters from K2 campaign 4 - Johnson, Marshall C.; Gandolfi, Davide; Fridlund, Malcolm; Csizmadia, Szilard; Endl, Michael; Cabrera, Juan; Cochran, William D.; Deeg, Hans J.; Grziwa, Sascha; Ramírez, Ivan; Hatzes, Artie P.; Eigmüller, Philipp; et al. (The astronomical journal, 2016)
We confirm the planetary nature of two transiting hot Jupiters discovered by the Kepler spacecraft’s K2 extended mission in its Campaign 4, using precise radial velocity measurements from FIESNOT, HARPS-N@TNG, and the coudé spectrograph on the McDonald Observatory 2.7 m telescope. K2-29 b (EPIC 211089792b) transits a K1V star with a period of 3.2589263 ± 0.0000015 days; its orbit is slightly eccentric (). It has a radius of RJ and a mass of MJ. Its host star exhibits significant rotational variability, and we measure a rotation period of days. K2-30 b (EPIC 210957318 b) transits a G6V star with a period of 4.098503 ± 0.000011 days. It has a radius of RJ and a mass of MJ. The star has a low metallicity for a hot Jupiter host, .
Gesehen am 06.05.2020